1989
DOI: 10.1164/ajrccm/139.3.595
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health of a Population Living Downwind from Natural Gas Refineries

Abstract: Since 1958 there has been a perception of excess illness in a rural Canadian population living downwind from two natural gas refineries, the emissions of which contain mostly sulfur dioxide but also hydrogen sulfide. To determine if there was an excess of adverse health outcomes in the population exposed (defined by place of residence), a health survey was undertaken in 1985 in this area and in one unexposed to emissions but demographically similar. Participation was 92% from both the exposed population (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 3 publications
4
23
0
Order By: Relevance
“…These results are in some ways consistent with those reported by Dales et al [1989] in southern Alberta. The investigators found an increase in respiratory symptoms in children aged 5-13 and in never-smokers over the age of 14 who lived downwind from a natural gas refinery.…”
Section: Discussionsupporting
confidence: 92%
“…These results are in some ways consistent with those reported by Dales et al [1989] in southern Alberta. The investigators found an increase in respiratory symptoms in children aged 5-13 and in never-smokers over the age of 14 who lived downwind from a natural gas refinery.…”
Section: Discussionsupporting
confidence: 92%
“…industrial pollution have consistently indicated a relationship between air pollution and respiratory symptoms such as bronchitis or wheeze and cough in children. [2][3][4][5][6][7] Asthma rates among children, however, were not found to be elevated in these studies. Similarly, in adults, community-based studies have found an association between air pollution and bronchitis, but not asthma.…”
Section: Discussionmentioning
confidence: 59%
“…Adults did not show this effect. Neither adults nor children showed a corresponding difference in pulmonary function (90).…”
Section: Studies Of Air Quality and Human Healthmentioning
confidence: 83%
“…They do not relate to the period of the study and cannot be correlated to symptoms occurring at the time of the study. Despite these limitations, the authors used the data to construct a crude exposure gradient and reported a possible association (90).…”
Section: Studies Of Air Quality and Human Healthmentioning
confidence: 99%